USM APPRECIATES VISIT OF HEALTH MINISTER TO HUSM - MPRC, Pusat Media & Perhubungan Awam (USM, 2014)
KOTA BHARU, 31 December 2014 Universiti Sains Malaysia (USM) highly appreciated the visit of the Minister of Health Malaysia, Datuk Seri Dr. S. Subramaniam to the Hospital Universiti Sains Malaysia (HUSM) yesterday. USM ViceChancellor, Professor Dato’ Dr. Omar Osman said the visit meant a lot to USM.